Unlocking play willingness: the dual pathways of curiosity drive and downward social comparison in game advertising - Zetian, Dai; Juan, Xue; Jiaxin, Du; Hoe Tan, Wee (Frontiers in Psychology, 2024)
The integrity and clarity of information have long been regarded as the cornerstones of advertising strategy. However, recent game advertising has taken a different approach. Specifically, incomplete game videos, especially those showcasing losing gameplay, are more likely to stimulate players’ interest compared to complete videos of winning gameplay. This study, through five experiments, uncovers a dual-pathway mechanism behind this phenomenon. Firstly, information gaps resulting from incomplete videos trigger curiosity drive, compelling viewers to seek more information and reinforcing their willingness to engage in gaming. Secondly, witnessing failures in game demonstrations activates components of downward social comparison and competitive motivation. These findings offer valuable insights into the complex dynamics of game advertising, shedding light on the effects of information gaps, curiosity, and social comparison. They provide valuable implications for advertising strategies within the gaming industry.